Distribution Spread and Environmental Risk Status of Pb, Cd And Cr in Soils of an Open-Air Waste Dumpsite along Tombia/Amassoma Road in Yenagoa Metropolis - Aigberua Omozemoje Ayobami; Okumoko Pearce Dokumo (Journal of Plant and Animal Ecology, 2020)
In spite of the popularity of open-air waste dumping in Nigeria, it remains a relatively less effective waste management option across the globe because of its associated environmental impacts which includes the release of green house gases (GHGs), persistent organic pollutants (POPs), and metal micro-pollutants amongst others. This study aims to assess the potential environmental risks associated to metals released and vertically delineated across the soil profile within surroundings of dumpsite. Heavy metals in soil samples were acid-digested using the aqua-regia mixture of hydrochloric and nitric acid, followed by instrumentation analysis using the GBC 908 PBMT model atomic absorption spectrophotometer. Contaminated sites showed metal concentrations ranging from 1.493 to 109.460 mg/kg, 0.133 to 4.237 mg/kg, and 5.200 to 25.367 mg/kg for lead, cadmium and chromium respectively, with location 1 land area showing the most contamination. Only soil chromium was observed within regulatory stipulations in all cases. There was significant variation (p < 0.05) between the different sample locations, thereby indicating variations in composition of dumped wastes. Lead and cadmium showed the strongest positive correlation (r = 0.855, p < 0.01) and the application of some heavy metal pollution indicators revealed relatively higher metal loads and degree of contamination, as well as depicting potential ecological risk for soils of location 1. The significant heavy metal contamination of soils in the Tombia-Amassoma waste dumpsite requires that the local environmental sanitation and regulatory authorities take necessary remedial action to forestall the escalation of public health concerns that may emanate from this open-air dump.
Keywords: Tombia-Amassoma waste dumpsite